1988
DOI: 10.1128/jvi.62.9.3156-3166.1988
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class II-regulated immunity to murine leukemia virus protects against early T- but not late B-cell lymphomas

Abstract: We studied the relative importance of class I and class II major histocompatibility complex (MHC) immunoregulation in the control of Tand B-cell lymphomas induced by murine leukemia virus. Previously, we have described a mink cell focus-inducing (MCF) murine leukemia virus, MCF 1233, which induces not only lymphoblastic T-cell lymphomas but also follicle center cell or lymphoblastic B-cell lymphomas. We now report that the outcome of neonatal infection with MCF 1233 in H-2-congenic C57BL/10 and C57BL/6 mice is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…How retroviruses adapt to the environment encountered in a newly infected host has not been well studied. Immune responses to retroviral envelope proteins are regulated by MHC genes (45)(46)(47). Passage of the Gross MuLV in BALB/c-H-2k mice results in the generation of variant viruses that have lost specific gp70en°epitopes (48) .…”
Section: Resultsmentioning
confidence: 99%
“…How retroviruses adapt to the environment encountered in a newly infected host has not been well studied. Immune responses to retroviral envelope proteins are regulated by MHC genes (45)(46)(47). Passage of the Gross MuLV in BALB/c-H-2k mice results in the generation of variant viruses that have lost specific gp70en°epitopes (48) .…”
Section: Resultsmentioning
confidence: 99%
“…We have been observing homozygous HLA associations in all major leukemias we have studied [1][2][3][4], and are surprised with the lack of attention to "homozygosity" in other genetic studies. The models we started with are the classic mouse leukemia studies, all of which have shown the importance of homozygosity for MHC alleles or haplotypes [22][23][24][25][26]. Heterozygosity for the susceptibility haplotype H-2 k in mouse leukemia and lymphoma does not modify the risk to these malignancies [22][23][24]37].…”
Section: Discussionmentioning
confidence: 99%
“…An ideal study should include as many as possible HLA loci and, whenever possible, selected non-HLA loci. The first truly molecular CML association study by Dorak et al [1] identified several independent markers, as is the case in murine leukemia [22][23][24][25][26]. The main MHC effect on the development of CML is on the age-at-onset as could be predicted from mouse leukemia studies [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in the in vivo biological relevance of the proposed selection mechanisms for tumor cells with respect to viral antigen and MHC cell surface expression. We previously described that the H-2 complex strongly influences lymphoma incidence after neonatal infection of C57BL/10 and C57BL/6 mice with mink cell focus-inducing (MCF) MuLV, MCF 1233 virus (25). T cell tumor resistance is dominant, maps to the class II MHC-encoding I-A region, and is associated with high titers ofanti-MuLV antibodies, which develop in the presence ofan adequate I-A-regulated antiviral Th response.…”
mentioning
confidence: 99%